(untitled) (Journal of Economic Research & Business Administration, 2016)
The analysis of recent Kazakhstan national currency tenge exchange rate devaluation causes. Tenge devaluation is considered by the authors, first of all, as a result of influence of prevailing international currency relations on Kazakhstan economy. This situation is substantiated by analysis of main macroeconomic and external economic indicators, the evaluation of influence of individual external and internal factors on these indicators is given. The first influenced fact on external markets is the slowdown of Russian economy and the decrease of ruble exchange rate, which significantly changed Kazakhstan economic development, as the cheap ruble contributes to Kazakhstan enterprises’ competitiveness decrease and increase of Russian import. The second fact is the Yuan devaluation, as China is the biggest player on metals market, and decrease of its economy can negatively influence on the level of metals prices, which are the big share of Kazakhstan export.